Sewage treatment plant sludge: a source of potential microorganism for citric acid production - Jamal, Parveen; Alam, Md. Zahangir; Ramlan, M.; Salleh, M.; M. Akib, Munirah (Science Publications, 2005)
This research emphasizes on the utilization of Sewage Treatment Plant (STP) sludge, which is an inexpensive and easily available raw material and a good source for growth of microorganisms because it has enough nutrients and trace elements. This can be considered as an alternative cost effective solution for waste management in addition to production of a value added product citric acid, one of the important chemicals used in various industrial processes. The isolation of filamentous fungi especially Aspergillus was done from STP sludge for better adaptability. Six strains of Aspergillus were isolated from STP sludge and identified using slide culture technique followed by image analysis. Four strains (SC906, A103, A2017 and A1020) were selected from lab stock. All strains were screened under controlled fermentation conditions such as pH range of 2-3, temperature 30°C and agitation 150 rpm, using 1% (w/w) of substrate (STP sludge), 2% (w/w) co-substrate (wheat flour) with inoculum’s size of 2% (spore mL‾1), using liquid state fermentation process for the maximum production of citric acid. Evaluation of fungal potentiality was done in terms of maximum citric acid production, biosolids production (TSS %) and chemical oxygen demand (COD) removal. Strain A-SS106 produced the highest concentration of citric acid (0.14 g L‾1), TSS (15.18 g L‾1) and COD removal (90.1%) on fourth day of fermentation.